Design and Off-Design Analysis of an ORC Coupled with a Micro-Gas Turbine. (September 2017) - Benato, Alberto; Stoppato, Anna; Mirandola, Alberto; Del Medico, Marco
Abstract: In the recent years, the possibility of recovering heat from gas turbine (GT) exhaust gases using Organic Rankine Cycles (ORC) have been largely explored. However, it is difficult to identify working fluids properly matching with micro-GT exhaust gases. For this reason, in the present work, the fluid selection and the plant layout optimization of an ORC which recovers the exhaust gases heat content of a 65 kW micro-gas turbine is presented. During the optimization process different plant configurations are considered: simple or regenerative and subcritical or transcritical. Exergy and economic analyses are also performed to estimate the exergy destruction rate and evaluate the economic feasibility of the optimized solutions. In order to find out the most suitable ORC unit and its behaviour, an off-design analysis is also performed using the commercial software Aspen Plus. Adopting a management strategy that maintains the turbine inlet temperature constant the best off-design performance is reached with Cyclopentane as working fluid.